O tratamento com implantes dentários para pacientes com hiv é uma realidade? - Santiago Júnior, Joel Ferreira [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Moraes, Sandra Lúcia Dantas de; Shinohara, Élio Hitoshi [UNESP] (My University, 2012)
Patients infected with HIV can present several complications related to oral health. Today, the reduction of morbidity and mortality is evidenttreatment with antiviral enhances the quality of life of patients. The increase in comfort, stability, function and improving quality of life have led these patients to seek treatment with osseointegrated implants. This study aimed to discuss, based on the literature, the rehabilitation treatment with osseointegrated implants in patients HIV positive. For this we carried out a literature review including the subject in the databases: PubMed, Cochrane, ISI Dentistry and Oral Science in the last 20 years. The issue was addressed for the first time in 1998, describing a clinical case, the patient had successful rehabilitation with osseointegrated implants. However, the literature states that the indications must be carefully analyzed (2007), since there are few prospective controlled studies. There is doubt as to the use of dental implant therapy in patients with HIV-positive, and the complications are related to the patient’s systemic condition. It is essential to understand the clinical manifestations and complications of the disease before the implant therapy. It is observed that the dental implant therapy in patients with HIV positive is a predictable treatment option, it´s need an adequate control of oral and systemic conditions, and studies with larger sample, longer follow-up and randomized studies are important for evaluating the success therapy.

O paciente infectado com o HIV pode apresentar diversas complicações relacionadas à saúde oral. Hoje, a redução da morbidade e mortalidade da doença é evidente, o tratamento com antiviral amplia a qualidade de vida dos pacientes. O aumento do conforto, estabilidade, função e melhoria na qualidade de vida têm levado estes pacientes à procura do tratamento com implantes osseointegráveis. Este trabalho objetivou discutir, com base na literatura, o tratamento reabilitador com Implantes Osseointegrados em pacientes HIV positivo. Para isso realizou-se uma revisão de literatura incluindo o tema nas bases de dados: Pubmed, Cochrane, ISI e Dentistry Oral Science nos últimos 20 anos. O tema foi abordado pela primeira vez em 1998, uma descrição de caso clínico, o paciente apresentou sucesso na reabilitação com implantes osseointegrados. No entanto, a literatura afirma que a sua indicação deve ser analisada com cautela (2007), já que existem poucos estudos prospectivos controlados. Existe dúvidas com relação à utilização da terapia com implantes dentários em pacientes com HIV positivo e, as complicações estão relacionadas à condição sistêmica do paciente. É indispensável para o clínico entender as manifestações e complicações da doença frente à terapia com implantes. Observa-se que, a terapia com implantes dentários em pacientes com HIV positivo é uma opção de tratamento previsível, é necessário um adequado controle das condições orais e sistêmicas e, estudos com casuística ampliada, acompanhamento longo e, randomizados são importantes para avaliação do sucesso da terapia.
Is the treatment of dental implants for patients with hiv a reality?
Keywords: Dental implant; HIV seropositivity; Implante dentário; Soropositividade para HIV